Anti-inflammatory cytokines content in different clinical uveitis course complicated by the optic nerve inflammation (Ukrainian Journal of Ophthalmology, 2026)
The purpose of this work was to study the content of anti-inflammatory cytokines interleukin-4 (IL-4) and interleukin-10 (IL-10) in different clinical uveitis course complicated by the optic nerve inflammation.Material and Methods. 132 patients with uveitis complicated by the optic nerve inflammation in the active stage were examined and treated.  Anti-inflammatory cytokines (IL-4, IL-10) were determined in the blood serum of all the patients by immunoenzyme method.Results. It was found that the content of interleukin-4 in uveitis complicated by the inflammation of the optic nerve was 2.3 times and interleukin-10 - 2.6 times lower in comparison with control group, respectively (p
Keywords: uveitis; complicated by the inflammation of the optic nerve; interleukin-4; interleukin-10